Galectins-1 and-3 Increase in Equine Post-traumatic Osteoarthritis - Reesink, Heidi L.; Nixon, Alan J.; Su, Jin; Liu, Sherry; Sutton, Ryan M.; Mann, Sabine; Watts, Ashlee E.; Peterson, Ryan P. (Frontiers in Veterinary Science, 2018)
Galectins are potent regulators of cell adhesion, growth and apoptosis in diverse cell types, including chondrocytes and synovial fibroblasts. Elevations in synovial fluid galectin-3 have been observed in rheumatoid arthritis, juvenile idiopathic arthritis and experimental inflammatory arthritis in animal models, whereas galectin-1 is thought to be protective. Less is known about galectins-1 and-3 in osteoarthritis (OA). Therefore, the purpose of this study was: (1) to determine whether galectin-1 and-3 synovial fluid concentrations and synovial membrane and cartilage histochemical staining were altered following osteochondral injury in an experimental equine osteoarthritis (OA) model and (2) to measure galectin-1 and-3 mRNA expression and synovial fluid concentrations in naturally occurring equine carpal OA. Synovial fluid galectin-1 and-3 concentrations were quantified using custom ELISAs in two research horse cohorts undergoing experimental OA induction (n = 5 and 4) and in a cohort of horses with naturally occurring carpal OA (n = 57). Galectin mRNA expression in synovial membrane and cartilage tissue obtained from carpal joints of horses with naturally occurring OA was measured using RT-qPCR, and galectin immunostaining was assessed in synovial membrane and osteochondral tissues in the experimental model (n = 5). Synovial fluid galectin-1 and-3 concentrations increased following experimental carpal osteochondral fragmentation. Cartilage galectin-1 mRNA expression increased with OA severity in naturally occurring disease. The superficial zone of healthy articular cartilage stained intensely for galectin-3 in sham-operated joints, whereas galectin-1 staining was nearly absent. Chondrocyte galectin-1 and-3 immunoreactivity increased following cartilage injury, particularly in galectin-1 positive chondrones. Galectins-1 and-3 are present in healthy equine synovial fluid and increase following post-traumatic OA. Healthy superficial zone chondrocytes express galectin-3, whereas galectin-1 chondrocyte staining is limited predominantly to chondrones and injured cartilage. Further work is needed to clarify the functions of galectins-1 and-3 in healthy and OA joints.